Factors influencing the expression of human directed dog aggression. A qualitative study of professional opinion - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Observation error appears to explain the perception of earlier maturation in Atlantic cod following the industrialised fishing - Olav Sigurd Kjesbu; Ine Elise Moksness; Shuyang Ma; Jennifer A. Devine; Maud Alix; Johanna Fall; Côme Denechaud; Thassya C. dos Santos Schmidt; Anders Thorsen; Geir Huse; Daniel Howell; Knut Korsbrekke (Progress in Oceanography, 2025)

Adding splines to the SAM model improves stock assessment - Silius M. Vandeskog; Magne Aldrin; Daniel Howell; Edvin Fuglebakk (Fisheries Research, 2025)

Rapamycin Treatment Reduces Brain Pericyte Constriction in Ischemic Stroke - Daniel J. Beard; Lachlan S. Brown; Gary P. Morris; Yvonne Couch; Bryan A. Adriaanse; Christina Simoglou Karali; Anna M. Schneider; David W. Howells; Zoran B. Redzic; Brad A. Sutherland; Alastair M. Buchan (Translational Stroke Research, 2025)
The contraction and subsequent death of brain pericytes may play a role in microvascular no-reflow following the reopening of an occluded artery during ischemic stroke. Mammalian target of rapamycin (mTOR) inhibition has been shown to reduce motility/contractility of various cancer cell lines and reduce neuronal cell death in stroke. However, the effects of mTOR inhibition on brain pericyte contraction and death during ischemia have not yet been investigated. Cultured pericytes exposed to simulated ischemia for 12 h in vitro contracted after less than 1 h, which was about 7 h prior to cell death. Rapamycin significantly reduced the rate of pericyte contraction during ischemia; however, it did not have a significant effect on pericyte viability at any time point. Rapamycin appeared to reduce pericyte contraction through a mechanism that is independent of changes in intracellular calcium. Using a mouse model of middle cerebral artery occlusion, we showed that rapamycin significantly increased the diameter of capillaries underneath pericytes and increased the number of open capillaries 30 min following recanalisation. Our findings suggest that rapamycin may be a useful adjuvant therapeutic to reduce pericyte contraction and improve cerebral reperfusion post-stroke.

Risk factors for human-directed aggression by dogs: The human side of the problem. A two-part systematic review and narrative synthesis - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2025)

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Naturally occurring radioactive materials in offshore infrastructure: Understanding formation and characteristics of baryte scale during decommissioning planning - Amy MacIntosh; Daniel T. Oldfield; Dioni I. Cendón; Andrew D. Langendam; Nicholas Howell; Daryl L. Howard; Tom Cresswell (Journal of Hazardous Materials, 2024)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Diversity and transparency in gynecologic oncology clinical trials - Mary Katherine Montes de Oca; Elizabeth P. Howell; Daniel Spinosa; Hope Knochenhauer; Benjamin J. Peipert; Eric Severson; Shakti Ramkissoon; Tomi F. Akinyemiju; Rebecca A. Previs (Cancer Causes & Control, 2023)

Strength and consistency of density dependence in marine fish productivity - Anna Rindorf; Mikael van Deurs; Daniel Howell; Eider Andonegi; Aaron Berger; Bjarte Bogstad; Noel Cadigan; Bjarki Þór Elvarsson; Niels Hintzen; Marie Savina Roland; Marc Taylor; Vanessa Trijoulet; et al. (Fish and Fisheries, 2022)
The correct prediction of the shape and strength of density dependence in productivity is key to predicting future stock development and providing the best possible long‐term fisheries management advice. Here, we identify unbiased estimators of the relationship between somatic growth, recruitment and density, and apply these to 80 stocks in the Northeast Atlantic. The analyses revealed density‐dependent recruitment in 68% of the stocks. Excluding pelagic stocks exhibiting significant trends in spawning stock biomass, the probability of significant density dependence was even higher at 78%. The relationships demonstrated that at the commonly used biomass limit of 0.2 times maximum spawning stock size, only 32% of the stocks attained three quarters of their maximum recruitment. This leaves 68% of the stocks with less than three quarters of their maximum recruitment at this biomass limit. Significantly lower recruitment at high stock size than at intermediate stock size was seen in 38% of the stocks. Density dependence in late growth occurred in 54% of the stocks, whereas early growth was generally density‐independent. Pelagic stocks were less likely to exhibit density dependence in recruitment than demersal and benthic stocks. We recommend that both the degree to which productivity is related to density and the degree to which the relationship changes over time should be investigated. Both of these aspects should be considered in evaluations of whether sustainability and yield can be improved by including density dependence in forecasts of the effects of different management actions.

Highly specific and rapid molecular detection of Candida glabrata in clinical samples - Oscar Hernández-Carreón; Cesia Hernández-Howell; Grecia Hernández-Hernández; M. Selene Herrera-Basurto; Blanca E. González-Gómez; Guadalupe Gutiérrez-Escobedo; Norma I. García-Calderón; Daniel Barrón-Pastor; Alejandro De Las Peñas; Irene Castaño (Brazilian Journal of Microbiology, 2021)

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Combining Ecosystem and Single-Species Modeling to Provide Ecosystem-Based Fisheries Management Advice Within Current Management Systems - Daniel Howell; Amy M. Schueller; Jacob W. Bentley; Andre Buchheister; David Chagaris; Matthew Cieri; Katie Drew; Mathieu G. Lundy; Debbi Pedreschi; David G. Reid; Howard Townsend (Frontiers in Marine Science, 2021)
Although many countries have formally committed to Ecosystem-Based Fisheries Management (EBFM), actual progress toward these goals has been slow. This paper presents two independent case studies that have combined strategic advice from ecosystem modeling with the tactical advice of single-species assessment models to provide practical ecosystem-based management advice. With this approach, stock status, reference points, and initial target F are computed from a single-species model, then an ecosystem model rescales the target F according to ecosystem indicators without crossing pre-calculated single-species precautionary limits. Finally, the single-species model computes the quota advice from the rescaled target F , termed here F eco . Such a methodology incorporates both the detailed population reconstructions of the single-species model and the broader ecosystem perspective from ecosystem-based modeling, and fits into existing management schemes. The advocated method has arisen from independent work on EBFM in two international fisheries management systems: (1) Atlantic menhaden in the United States and (2) the multi species fisheries of the Irish Sea, in the Celtic Seas ecoregion. In the Atlantic menhaden example, the objective was to develop ecological reference points (ERPs) that account for the effect of menhaden harvest on predator populations and the tradeoffs associated with forage fish management. In the Irish Sea, the objective was to account for ecosystem variability when setting quotas for the individual target species. These two exercises were aimed at different management needs, but both arrived at a process of adjusting the target F used within the current single-species management. Although the approach has limitations, it represents a practical step toward EBFM, which can be adapted to a range of ecosystem objectives and applied within current management systems.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Exploring Balanced Harvesting by Using an Atlantis Ecosystem Model for the Nordic and Barents Seas - Ina Nilsen; Jeppe Kolding; Cecilie Hansen; Daniel Howell (Frontiers in Marine Science, 2020)

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Deformation-related spectroscopic features in natural Type Ib-IaA diamonds from Zimmi (West African craton) - Karen V. Smit; Ulrika F. S. D’Haenens-Johansson; Daniel Howell; Lorne C. Loudin; Wuyi Wang (Mineralogy and Petrology, 2018)

Episodic diamond growth beneath the Kaapvaal Craton at Jwaneng Mine, Botswana - Michael U. Gress; Daniel Howell; Ingrid L. Chinn; Laura Speich; Simon C. Kohn; Quint van den Heuvel; Ellen Schulten; Anna S. M. Pals; Gareth R. Davies (Mineralogy and Petrology, 2018)

Introduction to Mammalian Genome special issue: inflammation and immunity in cancer - Andreas Behren; Daniel Speidel; George Kollias; Viive M. Howell (Mammalian Genome, 2018)

(±)-MDMA and its enantiomers: potential therapeutic advantages of R(−)-MDMA - Elizabeth G. Pitts; Daniel W. Curry; Karly N. Hampshire; Matthew B. Young; Leonard L. Howell (Psychopharmacology, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Including cetaceans in multi-species assessment models using strandings data: why, how and what can we do about it? - Saavedra Camilo; Cabrero Agueda; Cedeira Jose; Cerviño Santiago; Gago Jesus; González-Nuevo Gonzalo; Howell Daniel; López Alfredo; Pierce Graham; Read Fiona; Santos M. Begoña (Frontiers in Marine Science, 2014)

Unquantifiable uncertainty in projecting stock response to climate change: Example from North East Arctic cod - Daniel Howell; Anatoly A. Filin; Bjarte Bogstad; Jan Erik Stiansen (Marine Biology Research, 2013)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Role of dopamine transporters in the behavioral effects of 3,4-methylenedioxymethamphetamine (MDMA) in nonhuman primates - William E. Fantegrossi; Rayna M. Bauzo; Daniel M. Manvich; Jose C. Morales; John R. Votaw; Mark M. Goodman; Leonard L. Howell (Psychopharmacology, 2009)

Respiratory gene expression in soybean cotyledons during post-germinative development - Daniel O. Daley; Michael J. Considine; Katharine A. Howell; A. Harvey Millar; David A. Day; James Whelan (Plant Molecular Biology, 2003)

Modelling the influence of glacial isostasy on Late Weichselian ice-sheet growth in the Barents Sea - Daniel Howell; Martin J. Siegert; Julian A. Dowdeswell (Journal of Quaternary Science, 2000)